PENGARUH UNSUR SINEMATOGRAFI KDRAMA TERHADAP EFEK SINEMATERAPI PADA PEREMPUAN PEKERJA DI DKI JAKARTA - Fitriati, Trimalda Nur; Satrinia, Dwina; Sularso, Alva Nurvina; Rahmayadi, Gagas Ezhar; Azzahrah, Aprilia Putri (Universitas Mercu Buana, 2024)
As economic demands increase and gender roles change, the number of working women increases. The challenges faced by working women are also high, because they need to balance their roles as